2012
DOI: 10.1080/00194506.2013.735002
|View full text |Cite
|
Sign up to set email alerts
|

Reducibility Study of Egyptian Ilmenite Ore Briquettes and Powder with Coke Breeze at 800–1100°C

Abstract: Ilmenite ore fine and coke breeze as reduced material briquetted with different amounts of organic materials such as molasses or pitch were studied in this investigation. The produced briquettes in reasonable conditions were reduced in a nitrogen atmosphere at a temperature range of 800Á11008C to determine the factors controlling the reduction and to determine the controlling mechanism. Also ilmenite ore fines with coke breeze were reduced at the same temperature range in a nitrogen atmosphere without the briq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…X-ray diffraction analysis of Rosetta ilmenite ore concentrate is shown in Fig. 1 Rosetta ore concentrate mainly consist of ilmenite Fe 2 TiO 3 , pseudo-rutile Fe 2 Ti 3 O 9 , hematite Fe 2 O 3 and a minor quantity of rutile [11,12].…”
Section: Ilmenite Orementioning
confidence: 99%
“…X-ray diffraction analysis of Rosetta ilmenite ore concentrate is shown in Fig. 1 Rosetta ore concentrate mainly consist of ilmenite Fe 2 TiO 3 , pseudo-rutile Fe 2 Ti 3 O 9 , hematite Fe 2 O 3 and a minor quantity of rutile [11,12].…”
Section: Ilmenite Orementioning
confidence: 99%
“…The composition of Rosetta ilmenite ore concentrate contains about 43.6% TiO 2 , 27.5% FeO and 20.9% Fe 2 O 3 . X-ray diffraction analysis of Rosetta ilmenite ore concentrate is shown inFigure 1, which indicated that the phases composing Rosetta ore concentrate mainly consist of ilmenite Fe 2 TiO 3 , Pseudorutile Fe 2 Ti 3 O 9 , hematite Fe 2 O 3 and a minor quantity of rutile according to the work which present in literatures[25] [26].…”
mentioning
confidence: 73%
“…Reduction of the prepared briquettes under hydrogen gas was done using TGA apparatus [13][14][15][16][17][18][19]. The sample was placed in a Ni-Cr basket, which was suspended below the electronic balance by Ni-Cr wire.…”
Section: Briquette Reduction Proceduresmentioning
confidence: 99%